2020
DOI: 10.3390/nu12092684
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Body Mass Index and Breastfeeding Non-Initiation and Cessation: A Quantitative Review of the Literature

Abstract: This study aims to investigate which maternal body mass index (BMI) categories are associated with the non-initiation or cessation of breastfeeding (BF) based on a quantitative review of the literature. We searched Ovid MEDLINE and EBSCO CINAHL for peer-reviewed articles published between 1946 (MEDLINE) or 1981 (CINAHL), and 2019. Selected studies were either cross-sectional or cohort studies, of healthy mothers and infants, that reported nutrition method (exclusive/full or any) and period (initiation/duration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 119 publications
(497 reference statements)
3
4
0
Order By: Relevance
“…Women with larger bodies (i.e., higher BMI) at the time of the study visit were less likely to practice EBF beyond 1 month, a finding in accord with previous reports (52,53). Since higher maternal BMI or higher fat mass percentage have been associated with shorter duration of EBF and delayed lactogenesis (53), physical, hormonal or socio-cultural factors are commonly proposed to explain such correlations (54).…”
Section: Discussionsupporting
confidence: 84%
“…Women with larger bodies (i.e., higher BMI) at the time of the study visit were less likely to practice EBF beyond 1 month, a finding in accord with previous reports (52,53). Since higher maternal BMI or higher fat mass percentage have been associated with shorter duration of EBF and delayed lactogenesis (53), physical, hormonal or socio-cultural factors are commonly proposed to explain such correlations (54).…”
Section: Discussionsupporting
confidence: 84%
“…According to Morrison's study [8], the two most common reasons for early cessation were perceived inadequate milk supply and maternal breast or nipple pain. Other studies [9,10] confirmed that obesity and smoking are risk factors. Social support characteristics (e.g., lack of breastfeeding support in the hospital, poor breastfeeding environment [11], and insufficient maternity leave [12]) have also been described as important reasons for early weaning.…”
Section: Introductionmentioning
confidence: 82%
“…Previously, these factors were accumulated as evidence reported as the socioeconomic factors of income and educational attainment. In addition, maternal obesity is an independent and important factor of exclusive breastfeeding, as we have already noted from a teaching hospital in Japan [ 9 ] and a meta-analysis about maternal overweight/obesity [ 10 ]. We previously reported that primiparous mothers of late childbearing ages (35 years or older) were at the most significant risk of not initiating exclusive breastfeeding [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are several reasons why it is difficult to maintain a high prevalence of breastfeeding. We previously reported that overweight or obese mothers, gestational week, cesarean section, nulliparity, older maternal age [ 9 , 10 ], and mental anxiety [ 11 ] were associated with an increased risk of not initiating/continuing breastfeeding.…”
Section: Introductionmentioning
confidence: 99%